Education on Making Native Chicken Feed Based on Taro in the Manuk Amertha Native Chicken Group in Asahduren Village - I Gusti Agus Maha Putra Sanjaya; I Nyoman Kaca; Ni Ketut Etty Suwitari (PT FORMOSA CENDEKIA GLOBAL, 2023)
Production costs in super native chicken farming can be reduced by making alternative feed. Community service carried out at the Manuk Amertha Native Chicken Group has contributed in the form of an increase in partner knowledge in terms of formulating native chicken rations, especially with feed ingredients that are widely available in the surrounding environment, as well as increasing the ability of farmers to make alternative taro-based chicken feed. This activity was carried out on 6 May 2023 using explorative methods and active community participation. The tangible results of this service activity are that partners have good knowledge and understanding of the preparation of nutritional formulations of native chicken feed, and are able to make alternative feed based on taro so that it can reduce the business operational costs of each group member.